Alcohol consumption is associated with decreased risk of rheumatoid arthritis: results from two Scandinavian case–control studies. Issue 2 (5th June 2008) - Källberg, H; Jacobsen, S; Bengtsson, C; Pedersen, M; Padyukov, L; Garred, P; Frisch, M; Karlson, E W; Klareskog, L; Alfredsson, L
Abstract : Objectives: To determine the association between risk of rheumatoid arthritis (RA) and alcohol consumption in combination with smoking and HLA-DRB1 shared epitope (SE). Methods: Data from two independent case–control studies of RA, the Swedish EIRA (1204 cases and 871 controls) and the Danish CACORA (444 cases and 533 controls), were used to estimate ORs of developing RA for different amounts of alcohol consumed. Results: Alcohol consumption was significantly more common in controls (p<0.05) and dose-dependently associated with reduced risk of RA (p for trend <0.001) in both studies. Among alcohol consumers, the quarter with the highest consumption had a decreased risk of RA of the order of 40–50% compared with the half with the lowest consumption (EIRA, OR = 0.5 (95% CI 0.4 to 0.6); CACORA, OR = 0.6 (95% CI 0.4 to 0.9)). For the subset of RA that is seropositive for antibodies to citrullinated peptide antigens, alcohol consumption reduced the risk most in smokers carrying HLA-DRB1 SE alleles. Conclusions: The observed inverse association between alcohol intake and risk of RA and the recent demonstration of a preventive effect of alcohol in experimental arthritis indicate that alcohol may protect against RA. This highlights the potential role of lifestyle in determining the risk of developing RA, and emphasises the advice to stop smoking, but not necessarily to abstain from alcohol in order to diminish risk of RA. The evidence of potential RA prevention should prompt additional studies on how this can be achieved.